A Framework-Based Multi-Agent Coordination for Enhanced Microgrid Energy Management at the Secondary Control Layer - Yoldas, Y.; Onen, A.; Alawasa, K.; Haffar, A. El; Ahshan, R.; Islam, Md R.; Muyeen, S. M.; Noorfatima, N.; Jung, J. (IEEE Transactions on Applied Superconductivity, 2024)
The effective operation of a microgrid (MG) depends on seamless coordination among agents in energy management systems. A pivotal element in this coordination is the multi-agent coordinator, strategically positioned as an intermediate controller between the primary and tertiary control levels. Its role is to derive optimal setpoints from data obtained at the tertiary control level and convey them to the relevant agents at the primary control level. This study presents a novel optimization model for the multi-agent energy management system, aimed at enhancing real-time economic dispatch in the secondary control by managing active and reactive power. Instead of relying on a conventional centralized MG controller, the proposed framework employs multi-agent coordination to improve the reliability, stability, and economic performance of MG operations.
Keywords: Agent coordinator; Control layers; Control level; Energy; Management systems; Microgrid; Multi agent; Multi-agent coordinations; Multi-agent coordinator; Secondary control; energy management; microgrid; multi-agent coordinator; secondary control